2017
DOI: 10.1016/j.amepre.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Lessons Learned From a Prevention Research Center Partnership

Abstract: For more than a decade, the West Virginia Prevention Research Center, Mid-Ohio Valley Health Department, and the Wood County Schools have built and sustained a partnership to reduce health disparities and promote population health. Specifically, this partnership has contributed significantly to the peer-reviewed literature on children's physical activity, fitness, and academic achievement, as well as identifying possible areas for physical activity interventions (within the school and community settings) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This confluence of factors positions LPHAs as a promising pathway to scalability for school-and community-based initiatives. Others have been successful in partnering with LPHAs to implement school-based initiatives (40), although concrete assessments of implementation characteristics in applying such an approach are scant in the literature.…”
Section: Local Public Health Agenciesmentioning
confidence: 99%
“…This confluence of factors positions LPHAs as a promising pathway to scalability for school-and community-based initiatives. Others have been successful in partnering with LPHAs to implement school-based initiatives (40), although concrete assessments of implementation characteristics in applying such an approach are scant in the literature.…”
Section: Local Public Health Agenciesmentioning
confidence: 99%
“…The study leaders and executive committee identified 9 topical areas into which the activities were categorized: (1) support of frontline agencies, (2) food provision, (3) agriculture, (4) health care, (5) employment, (6) mental health, (7) education, (8) community health workers, and (9) support of community partners. The number of activities included in each topical area ranged from 2 (agriculture and mental health) to 8 (food provision).…”
Section: Engagement With Covid-19 Response Activitiesmentioning
confidence: 99%
“…6 As a result, PRCs are positioned to quickly and effectively respond to urgent health needs, coordinating the provision of health and social services and collecting data to inform efforts in health promotion and disease prevention. [7][8][9][10] By understanding community priorities and assets before a crisis and leveraging community partnerships, PRCs can mobilize resources to understand the challenges and quickly collaborate with local communities to facilitate a response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This con uence of factors positions LPHAs as a promising pathway to scalability for school-and community-based initiatives. Others have been successful in partnering with LPHAs to implement school-based initiatives (Cottrell et al, 2017), although concrete assessments of implementation characteristics in applying such an approach are scant in the literature.…”
Section: Local Public Health Agenciesmentioning
confidence: 99%